IS EDUCATIONAL LEVEL OF ASHA MATTERS FOR THEIR EFFECTIVE FUNCTIONING? A CROSS- SECTIONAL STUDY IN EASTERN UTTAR PRADESH - Kansal, Sangeeta; Kumar, Santosh; Kumar, Alok (Indian Journal of Community Health, 2012)
Background: The actualisation of the goal of NRHM depends on the functional efficacy of the ASHA as the grassroot health activist. Methods: This is cross sectional study, based on a sample of 135 ASHA working in different areas of Chiraigaon Block of Varanasi in eastern Uttar Pradesh (UP). ASHA were interviewed to ascertain the role of educational level on their effective functioning. Results: In the present study about one third of ASHA had schooling up to class eight, 36.6% High School and 22.2% intermediate, and 10.4 % were graduates. Statistically significant association was observed between educational level & practices undertaken by ASHA in the community. At the same time the findings also indicate that ASHA educated up to class eight faces difficulty in filling Village Health Index Register provided to them. Conclusions: The study recommends that if it is difficult to upgrade the minimum educational level for the appointment of ASHA, there is a strong need of regular training & monitoring of ASHA from other functionaries. Village Health Index Register should be simplified so that they can maintain the record properly. Otherwise, if women with good education have joined come forth to work as ASHA, this would certainly improve the service delivery.